2016
DOI: 10.5812/ijhrba.27264
|View full text |Cite
|
Sign up to set email alerts
|

Opium Consumption Prevalence Among Patients With Ischemic Stroke Compared With Healthy Individuals in Iran

Abstract: Background: One of the supposed risk factors of ischemic stroke is opium addiction, while the researches about its prevalence among patients with stroke are limited. Objectives: The aim of this study was comparing the prevalence of opium addiction between subjects with thrombotic ischemic stroke and healthy individuals. Patients and Methods: In this comparative cross-sectional study carried out in a number of academic hospitals affiliated to Guilan University of Medical Science in the north of Iran from April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Opioid dependence (OD) was defined according to the Diagnostic and Statistical Manual of Mental Disorders, fourth edition, text revision (DSM-IV-TR) (304.00, opium dependence): continued for at least one year (via inhalation or oral ingestion). 22 Furthermore, total-cholesterol (TC), highdensity lipoprotein-cholesterol (HDL-C), low-density lipoprotein-cholesterol (LDL-C), triglycerides (TG), and FBG levels in serum were further considered.…”
Section: Definitionsmentioning
confidence: 99%
“…Opioid dependence (OD) was defined according to the Diagnostic and Statistical Manual of Mental Disorders, fourth edition, text revision (DSM-IV-TR) (304.00, opium dependence): continued for at least one year (via inhalation or oral ingestion). 22 Furthermore, total-cholesterol (TC), highdensity lipoprotein-cholesterol (HDL-C), low-density lipoprotein-cholesterol (LDL-C), triglycerides (TG), and FBG levels in serum were further considered.…”
Section: Definitionsmentioning
confidence: 99%
“…Table 1 demonstrates the characteristics of included studies (3,(17)(18)(19)(20)(21)(22)(23). Six (75%) studies included in the qualitative analysis were case-control, while the remaining two records were cohort studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Six included studies evaluated the relationship between opium consumption and stroke (18)(19)(20)(21)(22)(23). The outcome of four papers was the diagnosis of ischemic stroke (18,20,22,23), while in two other, indices regarding the formation of ischemic plaque (21) and diagnosis of any kind of stroke (19) were the outcome. Four (18,19,21,22) out of these six studies revealed at least a significant measure concerning the association between stroke and opium use.…”
Section: Qualitative Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…troke is one of the diseases affecting health worldwide and one of the main causes of long-term disabilities [1]. The prevalence of this disease in Iran is 372 people per 100,000 people [2].…”
Section: Introductionmentioning
confidence: 99%